Interdependency of Culture and Nature in Tamba Kaiten: An Eco-Critical Study - Tamang, Anju (Literary Studies, 2024)
Tamba Kaiten is a set of documentation on different folk traditions of the Tamang community which includes various ecological aspects, from folklore to rituals. Human activities which include diverse traditions and customs are associated with the natural world, especially indigenous ones. Being one of the most prominent yet disadvantaged ethnicities in Nepal, Santabir Lama (Pakhrin) has attempted to document the vanishing rites and traditions of the community despite being an Indian citizen but a Tamang nation by identity. The theoretical framework of eco-criticism plays an important role in establishing the relationship and interaction between human culture and ecology in different literature. Thus, Tamba Kaiten, which is an important set of songs by Tamba, the ethnic hero of the Tamang community who preserves history via songs, is better studied from an eco-critic perspective. Songs are the major medium of communication and preservation of culture along with entertainment functions. Tamba preserves and interprets the different phenomena on this Earth and the nature and interactions of Tamang and other communities or vice-versa with the means of songs. Therefore, songs have the potential to stand as literature in the folk domain. The story of the origin of the Earth and the Tamang community and its rites and rituals has an interdependent relationship with nature. Human activities are based on the natural world and their interactions with different agencies there; without human culture, nature wouldn’t have any meaning at all. Thus, it creates a need to study an ethnic folk tradition and literature to observe human culture’s interdependency on the environment.